Implementation of Study in Group to Optimize the Eleventh-Grade Science Students’ Participation in Learning - Melinda, Tania Marta; Tammu, Reisky Megawati (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2023)
Students’ participation in learning is the involvement of all students that is carried out responsibly to support the learning objectives. It can be seen from the indicators, such as asking questions, answering questions, doing assignments, and submitting assignments on time. However, it was found that there is a lack of participation in class XI Science students at a school in Jakarta, especially in the context of post-pandemic adjustment learning where learning is carried out offline and online. The solution implemented as an effort to optimize students’ participation in learning is through applying study in group method. The research method used is descriptive qualitative using an instrument in the form of a portfolio of Field Experience 2 Program activities consisting of observation sheets, mentor feedback, Lesson Plans (RPP), teaching reflections, and students’ assessment recaps. The research results show that student’s participation in learning can be optimized through the application of study in group method. It is seen from the several stages of its implementation, namely conveying procedures and regulations, forming heterogeneous groups with group leaders, delivering material, giving assignments and opportunities for discussion, group presentation sessions, question and answer sessions, and giving awards and conclusions. Suggestions for further research are the need to change the members in the study in group method regularly based on the topics and increase the time allocation for students to work on assignments.